Influence of biofilm-forming lactic acid bacteria against selected pathogenic bacteria - M.Kumar, Laavanya (2016)
The threat of pathogenic bacteria is a major health concern in the food and healthcare industry. Accordingly, numerous studies have shown that certain diseases are largely caused by the biofilms formed by the persistent pathogenic bacteria. By omitting the options of chemical preservatives or antibiotics, lactic acid bacteria (LAB) have shown great potential in inhibiting many of these pathogens. However, majority studies on antimicrobial properties of LAB use only the conventional planktonic forms of LAB. This study evaluates the potential application of LAB biofilms to control or inhibit the formation of biofilms by pathogenic bacteria. It was thus proposed that the biofilms formed by LAB could be a promising tool for the control of pathogen biofilm formation. In this study, biofilm-forming LAB was isolated from local fruits and dairy products. From the total of 21 distinguished LAB isolates, two isolates (Isolate Y1 and Isolate KF) were selected based on their prominent inhibition against test pathogens (using spot-on-agar method and agar-well-diffusion assay) and efficient biofilm production [using tissue culture plate (TCP) method] compared to other isolates. They were then identified as Lactobacillus casei Y1 and Lactobacillus plantarum KF, respectively using 16S rDNA gene sequencing. The influence of incubation time, temperature and aeration on the biofilm production of Lb. casei Y1 and Lb. plantarum KF was also investigated using TCP method. For both the isolates, maximum biofilm production was found to be at the 48th h of incubation time, at the temperature of 35°C and under anaerobic condition. The inhibitory activity of both the selected LAB biofilms was evaluated against Methicillin-Resistant Staphylococcus aureus, MRSA (IMR code: S547), Listeria monocytogenes (IMR code: L10) and Escherichia coli O157:H7 (IMR code: E187), using Lb. plantarum ATCC 8014 as the reference strain, preliminarily at the 48th hour. However, from the initial finding, only biofilms of MRSA (S547) were found to be susceptible by all the selected LAB biofilms. As such only MRSA (S547) was selected for the detailed study of their biofilm inhibition using biofilms of LAB. When LAB biofilms and MRSA (S547) were co-cultured, both LAB biofilms showed significant potential in reducing the adherent and planktonic population of MRSA (S547). Lactobacillus casei Y1 showed the highest reduction of MRSA biofilms, by 3.53 log at 48 hours while Lb. plantarum KF records the highest reduction of 2.64 log at 36 hours. In inhibiting planktonic population of MRSA (S547), both Lb. casei Y1 and Lb. plantarum KF biofilms recorded their maximum reduction of 4.13 log and 3.41 log at 24 hours, respectively. Despite their inhibitory effect being time-dependent, both LAB biofilms exhibited good potential in controlling the biofilm and planktonic population of MRSA (S547). The results from this study could highlight the importance of analysing biofilms of LAB to enhance their antimicrobial efficacy. Preferably, these protective biofilms of LAB could also be a better alternative to control the formation of biofilms by pathogens such as MRSA.